The paraphrase of Shem (NH VII, 1) : introduction, translation, and commentary - Roberge, Michel. (Nag Hammadi and Manichaean Studies, 2010)
This book presents the first comprehensive interpretation of the Paraphrase of Shem, Codex VII,1 in the Coptic Nag Hammadi Library. The lenghty introduction discusses the literary genre of the treatise, its plan and system, its situation among the Gnostic systems, its provenance and date. The translation sets out the text in paragraphs, with headings and subheadings. A short commentary follows the translation. The analysis of the system shows that the author is working from a model of the universe, whose principles have been drawn from Stoicism and Middle Platonism. While dipping into the springs of the major Sethian and Valentinian systems, the author follows his own way and offers an original system, anticipating in many respects Manichaeism.